Study of Reactivity Effect on Reactor Power by Using the Neutronic- Thermohydrolic Coupling (Baghdad Science Journal, 2012)
The study deals with reactivity insertion linear and non linear and/or Ramp reactivity expressed as a polynomial in time in the presence of two Feedback mechanisms, using the neutronic-thermohydraulic coupling in order to predict the neutron behavior as a function of time in terms of reactor power. Also, a comparative study has been achieved in the case of the presence of the feedback mechanisms. Insertion of Ramp reactivities in terms of polynomial in time to study the behavior of power and reactivity as a function of time in the presence of two feedback mechanisms (fuel and coolant) has been carried out and the results are displayed as plots, and showed this results corresponding with international results. The present study shows that the simulation of neutron time behavior is a vital tool to predict the behavior of reactivity and/or power as a function of time in case of insertion of negative or positive and/or Ramp reactivities in power reactor core for the case including feedback mechanism. Also, the simulation may be considered a unique technique to predict unexpected incident and/or accident that may occur in reactor power core in case of the availability of accurated input data.